Functionalization of π-activated alcohols by trapping carbocations in pure water under smooth conditions - Rosa Ortiz; Alessandro Koukouras; Eugenia Marqués-López; Raquel P. Herrera (Arabian Journal of Chemistry, 2020)
Acetic acid as catalyst in pure water was found to be an excellent reaction medium for the direct dehydrative functionalization of π-activated alcohols using a wide variety of interesting C-, P-, and S-centered nucleophiles, such as indoles, pyrrole, anilines, 1,3-dicarbonyl compounds, diphenyl phosphite and pyridine-2-thiol. The smooth reaction conditions, along with high yields, short reaction times, clean reaction crudes, an easy product isolation procedure, plus the reusability of the catalyst and the use of no excess of nucleophiles, make this approach an atom economical, green and appealing method to efficiently trap carbocations in pure water, leading to new Csp3X bonds (X = Csp2, Csp3, P and S). Keywords: π-Activated alcohols, Brønsted acid, Carbocation, Dehydrative substitution, Water